The Portrait Of The Human Spirit In Ulugbek Khamdam’s Novel “Balance” (Eurasian Research Bulletin, 2026)
This article psychologically sheds light on the depiction of the human psyche in Ulugbek Khamdam’s novel “Balance”, the conflicts in the characters’ inner worlds, spiritual quests, and the personal tragedy during the period of social change in the work, as well as the disruption of the balance between “I” and “the world”.